FORMULASI PRODUK KERUPUK DARI LIMBAH TULANG AYAM KAMPUNG: KAJIAN PROPORSI BAHAN DAN KONSENTRASI SODIUM TRIPOLYPHOSPHATE - Wisnu Prayogo (Jurnal Pangan dan Gizi, 2025)
The utilization of free-range chicken bones, a by-product of chicken meat processing, remains suboptimal despite their high nutritional content and potential for value-added food products. This study aimed to develop chicken bone crackers by determining the optimal proportions of ingredients (free-range chicken bone, wheat flour, and tapioca flour) and sodium tripolyphosphate (STPP) concentrations, evaluated based on nutritional composition, expansion ratio, and organoleptic properties. A randomized block design was employed with two factors: the proportion of chicken bone : wheat flour : tapioca flour (5:15:80; 10:20:70; and 15:25:60) and STPP concentration (0.1%, 0.25%, and 0.5%), each with three replications. Data were analyzed using analysis of variance (ANOVA) followed by Duncan’s Multiple Range Test (DMRT). Organoleptic evaluation was conducted by 25 semi-trained panelists, assessing color, aroma, taste, and texture. The best treatment was determined using the Zeleny method. The results showed that ingredient proportions had a highly significant effect on nutritional content, expansion ratio, and the organoleptic properties of the cooked crackers. STPP concentration had a highly significant effect on the expansion ratio and texture. The best treatment was obtained at a proportion of 15:25:60 with an STPP concentration of 0.5%.